Effects of Glacier and Geomorphology on the Mechanism Difference of Glacier-Related Debris Flow on the South and North Banks of Parlung Zangbo River, Southeastern Tibetan Plateau - Jiajia Zhang; Jiankang Liu; Yuanling Li; Junchao Wang; Long Chen; Bo Gao (Advances in Civil Engineering)
Alpine glaciers are vulnerable to climate changes, and their recession due to warming has already induced a large number of geohazards closely related to the glacial motion, such as debris flow. Strong coupling of the geology, geomorphology, climate, and glacial action controls the type, size, development, and frequency of debris flow along the Parlung Zangbo River, Southeastern (SE) Tibetan Plateau. Field investigation in recent years indicates that the north bank is prone to much more frequenter debris flows than the south bank. The sharp contrast between the two river banks is due to the different formation conditions of debris flows, especially glaciers and geomorphology. The present paper examines the differences in the glacier and geomorphology conditions for glacier-related debris flows to occur, through a combination of field investigation, interviews with local residents, and geomorphological parameter, and glacier distribution analysis in the ArcGIS platform. The result indicates that, compared to the south bank of the Parlung River, the north bank has more favorable conditions in the glacier and geomorphology south, which is more conducive to the occurrence of debris flow. In conclusion, three kinds of mechanisms due to different formation conditions, especially glacier and geomorphology, are analyzed. The glacier-related debris flows on the south and north banks occur through different mechanisms due to different formation conditions. The debris flows on the north bank primarily occur in modes I and III, while the south bank is dominated by modes II and III debris flows. Based on the result, effective measures are proposed for mitigating damage to roads and railways within this area.